Artificial neural networks in energy applications in buildings - Kalogirou, Soteris A. (My University, 2006)
Artificial neural networks (ANNs) are nowadays accepted as an alternative technology offering a way to tackle complex and ill-defined problems. They are not programmed in the traditional way but they are trained using past history data representing the behaviour of a system. They have been used in a number of diverse applications. Results presented in this paper are testimony to the potential of artificial neural networks as a design tool in many areas of building services engineering.
Keywords: Artificial neural networks; Energy prediction; Building applications